Optimizing low-carbon strategies in dual-channel supply chains: A quantum game perspective - Qi Yao; Yanhui Li; Huan Gao (PLoS ONE, 2025)
The carbon emission management and resource allocation optimization of dual-channel supply chain are of great significance for promoting low-carbon economy and improving supply chain efficiency. In contrast to conventional game theory, Quantum game theory can describe the cooperation and competition of online and offline channels more flexibly through quantum entanglement, so as to overcome the limitations of traditional game theory. We study the application of quantum game theory in low-carbon economy and pricing strategies, and explore how to optimize pricing strategies and improve the low-carbon levels under different entanglement. Therefore, considering consumers’ preference for low-carbon products, this paper establishes a quantum game model to encourage low-carbon actions in the dual-channel supply chain. We discuss three models of centralized decision making, decentralized decision and quantum equilibrium, and analyze the optimal strategies of manufacturers under different entanglement. The results show that quantum game theory has significant advantages in low-carbon dual-channel supply chains. With the increase of quantum entanglement, the low-carbon production level and corporate profitability in the supply chain have been significantly improved, especially under the decentralized decision-making framework, quantum game equilibrium can promote low-carbon behavior and improve profits more than traditional game models. When the degree of entanglement approaches infinity, the total profit of supply chain enterprises using quantum strategy exceeds the profit of supply chain enterprises with centralized decision-making. It is important to note that quantum entanglement can significantly reduce the optimal wholesale and online sales prices for manufacturers. At the same time, the impact of quantum game on manufacturers’ decision-making is more significant than that on retailers, indicating that quantum entanglement shows different sensitivities in influencing the pricing and profitability strategies of different supply chain participants. This finding provides a new theoretical perspective and practical guidance for pricing strategies, firm cooperation and competition in low-carbon supply chains.